Activation of NFAT signaling establishes a tumorigenic microenvironment through cell autonomous and non-cell autonomous mechanisms - Tripathi, Piyush (2013)
NFAT upregulation has been linked to cellular transformation intrinsically, but it is unclear whether and how tissue cells with NFAT activation change the local environment for tumor initiation and progression. Direct evidence showing NFAT activation initiates primary tumor formation in vivo is also lacking. Using inducible transgenic mouse systems, we show that tumors form in a subset of, but not all, tissues with NFATc1 activation, indicating that NFAT oncogenic effects depend on cell types and tissue contexts. In NFATc1-induced skin and ovarian tumors, both cells with NFATc1 activation and neighboring cells without NFATc1 activation have significant upregulation of c-Myc and activation of Stat3. Besides known and suspected NFATc1 targets, such as Spp1 and Osm, we have revealed the early upregulation of a number of cytokines and cytokine receptors, as key molecular components of an inflammatory microenvironment that promotes both NFATc1(+) and NFATc1(−) cells to participate in tumor formation. Cultured cells derived from NFATc1-induced tumors were able to establish a tumorigenic microenvironment, similar to that of the primary tumors, in an NFATc1-dependent manner in nude mice with T cell deficiency, revealing an addiction of these tumors to NFATc1 activation and downplaying a role for T cells in the NFATc1-induced tumorigenic microenvironment. These findings collectively suggest that beyond the cell autonomous effects on the upregulation of oncogenic proteins, NFATc1 activation has non-cell autonomous effects through the establishment of a promitogenic microenvironment for tumor growth. This study provides direct evidence for the ability of NFATc1 in inducing primary tumor formation in vivo and supports targeting NFAT signaling in anti-tumor therapy.